The Influence of Digital Service Quality, Digital Transformation Readiness, And Academic Process Transparency on Academic Service Quality For Private Higher Education Students - Ninda Rachmawati; Firman Aziz; Rio Haribowo; Dewi Febriyanti; Diah Afrianti Rahayu; Desty Endrawati Subroto (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
This study attempts to analyze the influence of Digital Service Quality, Digital Transformation Readiness, and Academic Process Transparency on the Academic Service Quality perceived by students in private higher education in Indonesia. The methodology was quantitative and consisted of a survey applied to students with experience in several academic programs based on digital technology. The participants were selected by using purposive sample technique and the data were collected by using online questionnaires distributed by Google Forms. The data were analyzed using multiple linear regressions. The results show that Digital Service Quality, Digital Transformation Readiness and Academic Process Transparency positively and significantly impact Academic Service Quality perceived by students in private higher education institutions. Academic Process Transparency had more impact than the other two criteria in Academic Service Quality. The results show that the quality of the digital services, the institutional readiness for digital transformation and the openness and transparency of the academic processes are important factors in improving the quality of the academic services received by the students. The results suggest that the private higher education institutions should improve the reliability and usability of digital services, improve the organizational readiness for digital transformation, and provide transparent academic processes that are easy for learners to comprehend and monitor. It is expected that the use of these approaches will contribute to the improvement of the quality of service for students and the competitiveness of private higher education institutions in light of the growing digitalization of higher education.